Research on optimization of grouting treatment for underground mining goaf collapse based on 3-dimensional simulation - Teng, Lin; Xing, Xiansen; Sun, Changze; Liu, Zujian; Li, Xiaoshuang; Dong, Menglong (Frontiers in Earth Science, 2024)
The collapse of goaf is one of the most serious geological disasters in cities where underground mineral resources are mined. The ground subsidence caused by the goaf limits the social and economic development of the area, while also endangering the safety of residents and property near the mining area. At present, support and grouting treatment methods are commonly used for the treatment of goaf. The cost of support treatment is relatively high, and it is difficult to control the collapse of the deeper goaf. Grouting treatment is suitable for conducting detailed investigations of underground spaces. The cost of complete grouting is high, and the timing of grouting termination is difficult to control. This paper aims to explore the optimization of grouting efficiency in the treatment of underground subsidence in goaf areas using the reserved pillar mining method. Through the stability calculation of the goaf pillars and roof, it can be concluded that the goaf pillars are unstable pillars under current conditions and are prone to damage under load interference. At present, surface subsidence has occurred in the goaf and requires treatment.Consider the comparison between the collapse control effect under different grouting rates and the complete grouting, and ultimately select the condition of 90% grouting rate to achieve the control effect. This conclusion can provide a certain theoretical reference basis for the treatment of similar goaf collapse, and has certain practical significance.